162k views
0 votes
Simplify.
X² -16 divide X²-3x-4

1 Answer

4 votes

Answer:


((x+4))/((x+1))

Explanation:


(x^(2)-16)/(x^(2) -3x-4)

The numerator (upper half) can be squared:

knowing
x^(2) = x ×x

and knowing 16 = 4×4

we can simplify the numerator to:


((x+4)(x-4))/(x^(2) -3x-4)

Taking a look at the bottom:


x^(2) -3x-4

We can say:

a = 1

b = -3

c = -4

So we need two number than sum to -3 and multiply to -4:

-4 + 1 = -3

-4 * 1 = -4

The two numbers are -4 and 1 so:

(x - 4)(x + 1)

insert into equation:


((x+4)(x-4))/((x-4)(x+1))

We can remove (x-4) from top and bottom to get:


((x+4))/((x+1))

User Frank Wierzbicki
by
6.2k points